1977
DOI: 10.1002/bjs.1800641211
|View full text |Cite
|
Sign up to set email alerts
|

Wound implantation—a surgical hazard

Abstract: A review of the literature on wound implantation together with a report on an unusual case of irnplantation of squamous carcinoma at the site of a gastrostomy is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 32 publications
0
34
0
3
Order By: Relevance
“…2 This technique does not require Complications of percutaneous endoscopic gastrostomy are relatively uncommon, but include local infection, hemorrhage, dislodgment, peritonitis, bowel perforation and aspiration pneumonia 15 Another rare complication that appears to be becoming more prevalent is the metastatic implantation of tumor at the PEG tube site. 6,14 The first case of gastric and abdominal wall metastasis secondary to PEG placement in a patient with head and neck cancer was reported in 1989. 6,15 Since the introduction of this technique, there have been at least 23 case reports of tumor seeding at the gastrostomy site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 This technique does not require Complications of percutaneous endoscopic gastrostomy are relatively uncommon, but include local infection, hemorrhage, dislodgment, peritonitis, bowel perforation and aspiration pneumonia 15 Another rare complication that appears to be becoming more prevalent is the metastatic implantation of tumor at the PEG tube site. 6,14 The first case of gastric and abdominal wall metastasis secondary to PEG placement in a patient with head and neck cancer was reported in 1989. 6,15 Since the introduction of this technique, there have been at least 23 case reports of tumor seeding at the gastrostomy site.…”
Section: Discussionmentioning
confidence: 99%
“…6,14 The first case of gastric and abdominal wall metastasis secondary to PEG placement in a patient with head and neck cancer was reported in 1989. 6,15 Since the introduction of this technique, there have been at least 23 case reports of tumor seeding at the gastrostomy site. The mode of tumor spread to the gastrostomy site remains controversial and unproven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, tumor seeding of incisions has been implicated as contributing to local recurrence after surgical therapy for a variety of malignancies, with head and neck, breast, and colon being among the most frequently cited primary tumors. 13 Such occurrences are apparently very rare in gynecologic malignancies, but nonetheless case reports can be found for ovarian, endometrial, and cervical cancers.6.14-22 Dv orak,I4 in his review from 1930, references case reports from Olshausen in 1899 and 1902 describing probable implantation metastases in patients with both benign and malignant ovarian tumors, respectively, the latter occurring in a laparotomy scar. In 1965 Cole et al" described multiple subcutaneous metastases after paracentesis in a patient with advanced ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This type of metastasis was first described in 1977 in the skin and 1989 in the abdominal wall [27,28] . In a prospective trial with 50 patients suffering from oropharyngeal or esophageal cancer, Ellrichmann et al [29] demonstrated tumor seeding to the PEG insertion site in cytology in 9.4% of cases.…”
Section: Discussionmentioning
confidence: 99%